2014
DOI: 10.1097/shk.0000000000000186
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Vital Signs, Heart Rate Variability and Complexity, and Machine Learning for Identifying the Need for Lifesaving Interventions in Trauma Patients

Abstract: To date, no studies have attempted to utilize data from a combination of vital signs, heart rate variability and complexity (HRV, HRC), as well as machine learning (ML), for identifying the need for lifesaving interventions (LSIs) in trauma patients. The objectives of this study were to examine the utility of the above for identifying LSI needs and compare different LSI-associated models, with the hypothesis that an ML model would be superior in performance over multivariate logistic regression models. One hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 23 publications
6
42
0
Order By: Relevance
“…This study found the ML model to be superior to traditional logistic regression, which has already been observed in many studies [913]. For example, in the study of Churpek and al ., machine learning and logistic regression were compared to predict clinical deterioration in a large multicentric database of 269,999 patients.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study found the ML model to be superior to traditional logistic regression, which has already been observed in many studies [913]. For example, in the study of Churpek and al ., machine learning and logistic regression were compared to predict clinical deterioration in a large multicentric database of 269,999 patients.…”
Section: Discussionsupporting
confidence: 75%
“…Machine learning can establish powerful predictive models, and is already used by major companies such as Google and Facebook. Several studies have shown the superiority of machine learning over traditional logistic regression used in EuroSCORE II [913]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the findings in the current study should be tested for their accuracy to forecast as well as classify posttraumatic stress outcomes. ML classification algorithms have also been used to forecast the need for life-saving interventions among trauma patients based on vital signs and heart-rate while in transport to the hospital with very high accuracy (Liu, Holcomb, Wade, Darrah, & Salinas, 2014). This provides a useful example of how such methods can be used for efficient and accurate clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The Murphy Factor did not discriminate which of the six LSIs, one of which was blood transfusion, was indicated (21). In 96 prehospital trauma patients of whom 50% had any of six LSIs, a Murphy Factor more than 3 had AUROC of 0.62 for prediction of any LSI.…”
Section: Previous Lsi Outcome Prediction Studies Based On Vital Signsmentioning
confidence: 85%